1981
DOI: 10.1007/bf00149996
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of velocities in quiescent filaments

Abstract: Simultaneous observations of radial velocities in a 'quiescent' prominence seen in Ha on the disk and in the underlaying photosphere have been obtained in the Meudon Observatory: Doppler shifts in photospheric lines are weaker than in the surrounding regions (<0.3 kms-1); the scale of velocity structures is smaller (< 10 4 kin). The vertical component of velocities cannot be neglected. Ha Doppler shifts show that: (a) Highest velocities are often correlated with high brightness horizontal gradients, which sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…These flows have not, to the best of our knowledge, been previously described in over a century of ground-based observations. They are much higher velocity than the upflows measured in filament Ha Doppler observations (e.g., 3 km s ; Martres et al 1981) Ϫ1 but are perhaps consistent with later higher resolution observations (e.g., 5-20 km s ; Zirker et al 1998). It is unclear…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These flows have not, to the best of our knowledge, been previously described in over a century of ground-based observations. They are much higher velocity than the upflows measured in filament Ha Doppler observations (e.g., 3 km s ; Martres et al 1981) Ϫ1 but are perhaps consistent with later higher resolution observations (e.g., 5-20 km s ; Zirker et al 1998). It is unclear…”
Section: Discussionsupporting
confidence: 55%
“…Observations of filaments on the disk show that they are indeed resolvable into thin horizontal threads, often with measurable motions along the threads and up-or downflows in the footpoint regions (Kubota & Uesegi 1986;Zirker et al 1998;Lin et al 2005). However, observations of vertically striated or "hedgerow" prom- inences often show vertical filamentary downflows (Engvold 1981;Martres et al 1981) and vortices (Liggett & Zirin 1984). Reconciliation of the models with these observations of vertical and rotational flows remains a major goal of prominence physics.…”
Section: Introductionmentioning
confidence: 99%
“…Doppler measurements in these quiescent filaments A&A 542, A112 (2012) (e.g., Martres et al 1981;Schmieder et al 2010) have revealed that a wide range of velocities coexist in the same structure. For example, the recent study by Chae et al (2007) reported lineof-sight (LOS) velocities between ±5 km s −1 and ±15 km s −1…”
Section: Introductionmentioning
confidence: 98%
“…The mechanism generating such magnetic configurations must take into account photospheric motions. Martres et al (1981) found a photospheric velocity field beneath a filament in which lines of zero radial velocity were roughly perpendicular to the direction of the filament. Martin et al (1985) observed that the formation and evolution of filaments is linked to converging photospheric motions perpendicular to the polarity inversion line (PIL).…”
Section: Introductionmentioning
confidence: 99%